What are the determinants of non-performing financing in Islamic banks during Covid-19? - Rahmadany, An Nisaa'; Risfandy, Tastaftiyan; Harahap, Burhanudin (Universitas Sebelas Maret, 2023)
Several trading and banking sectors strive to survive the current pandemic. Despite the intense competition in the financial industry recently, Islamic banks have demonstrated remarkable growth. However, the issue of defaults in Islamic banks often arises, where debtors cannot repay the obtained financing, disrupting banking performance. This research investigates the factors influencing funding troubles in Islamic banks, especially during COVID-19. Specifically, this study examines whether factor-specific banks and macroeconomics in Islamic banks control troubled funding. The research utilizes quarterly data from Islamic banks in Southeast Asia (Malaysia and Indonesia) from 2020 to 2021. The findings indicate that liquidity risk, inefficiency, and economic growth do not significantly affect troubled financing in Islamic banks. At the same time, capital, profitability, and inflation significantly negatively impact funding troubles. These results recommend that Islamic banks increase their capital and profitability proportion to reduce the risk of funding trouble.